Changes in loading distribution in patients with Charcot foot during long-term follow-up - Anastasia G. Demina; Vadim B. Bregovskiy; Irina A. Karpova; Tatiana L. Tcvetkova (Сахарный диабет)
Background. The inactive stage of the diabetic Charcot arthropathy foot (CA) is characterised by fixed foot deformities and an absence of inflammation. However, it remains unclear if the shape of the foot and its biomechanics change during long-term follow-up. Aim. To evaluate changes in loading distribution of the affected foot, in patients with inactive CA, during long-term follow-up. Materials and methods. Twenty seven patients with unilateral inactive CA (19 females, 8 males) were studied. Computer pedography (emed AT, novel gmbh) was performed and baseline and the last studies were analysed. Maximal peak pressures (PP) were obtained for the first and the last studies and the percentage of the PP change was calculated for the total follow-up period and for periods: <24 months, 24–48 months, >48 months. Results. PP increased: under the hallux 50%; 1st metatarsal–30.7%; 2nd toe–20%; 2nd toe–6%; midfoot–9%. PP decreased under 3–5 toes up to 67%. Significant changes at the first period were found under 3–5 toes only (−62%). The increase in loading under the other parts of the foot appeared at 24 months; however, these changes became significant between 24 and 48 months and peaked after 48 months of follow-up. The maximal increase of PP was noticed under the hallux, the 2nd toe, metatarsals 1–3 and the midfoot. Conclusions. We revealed the gradual redistribution of PP, under the different parts of the foot, in patients with inactive CA. This redistribution reflects changes in the shape of the affected foot. The loading increased under the hallux, the 2nd toe and the corresponding metatarsals, 3rd metatarsal and midfoot, and decreased under the 3–5 toes. These changes increased during the follow-up, becoming more pronounced after 4 or more years. Our data may be useful for constructing custom-made footwear for patients with CA.